OPTIMIZATION MAINTENANCE PERFORMANCE LEVEL THROUGH COLLABORATION OF OVERALL EQUIPMENT EFFECTIVENESS AND MACHINE RELIABILITY - Rahman, Faisal; Sugiono, Sugiono; Sonief, Achmad As’ad; Novareza, Oyong (Journal of Applied Engineering Science, 2022)
Maintenance performance level (MPL) is an important part of the key performance indicator (KPI) to improve the effectiveness of machine maintenance which includes factors of overall equipment effectiveness-machine effectiveness (OEE-ME) and machine reliability (MR). The purpose of this paper is to optimize the value of the maintenance performance level (MPL) through the collaboration of overall equipment effectiveness-machine effectiveness (OEE-ME) and machine reliability (MR). The study began with collecting research data, namely machine operation, preventive maintenance, and corrective maintenance. The data is processed using the Pareto principle to determine the critical system based on failure frequency. The selected critical system is tested for probability distribution and machine reliability (MR) assessment with several predetermined maintenance time interval scenarios. The main result of this research is the optimal maintenance time interval is a better criterion than other criteria. The optimal maintenance time interval was chosen because it can meet the requirements of overall equipment effectiveness-machine effectiveness (OEE-ME) at a world-class maintenance performance level (MPL) with a value of 90.43%, and the proposed machine reliability (MR) is better than the initial machine reliability (MR) based on the failure ratio value. Therefore, it can be boldly stated that the collaboration of overall equipment effectiveness-machine effectiveness (OEE-ME) and machine reliability (MR) can influence and optimize the value of maintenance performance level (MPL), which has a strong correlation and significant impact.
Keywords: machine effectiveness, machine reliability, maintenance performance level, mobile crane, overall equipment effectiveness, optimization